Cerebrotendinous xanthomatosis in the Israeli Druze: molecular genetics and phenotypic characteristics. - Leitersdorf, E. (1994)
Cerebrotendinous xanthomatosis (CTX) is an autosomal recessive lipid-storage disease caused by mutations in the sterol 27 hydroxylase gene (CYP27). Clinically, a multitude of neurological, skeletal, and vascular manifestations are usually present. Premature atherosclerosis has been reported in CTX and may be related to the metabolic derangement caused by the deficiency of the enzyme. A CYP27 nonsense mutation created by the deletion of cytosine376 has been identified in four Israeli Druze CTX patients residing in the same village. Molecular screening for this mutation in families of two probands revealed a total of 10 homozygotes and 28 heterozygotes whose clinical and biochemical characteristics are described. Overall, except for tendon xanthomas, most of the clinical manifestations progress with age. The CYP27 mutation was associated with modest differences in the levels of plasma total cholesterol (TC) and LDL cholesterol (LDL-C). The distribution of plasma concentrations of TC and LDL-C in the CTX families was consistent with a polygenic model. A similar model that includes also the effects of the CYP27 genotypes was not better supported by the data. It may be concluded that, in CTX, the presence of a CYP27 mutation does not significantly affect the plasma concentrations of lipids and lipoproteins. Therefore, the reported increased prevalence of atherosclerosis in this disease must be related to other factors.